(untitled) (Journal of Training and Development, 2016)
The study was carried to explore the perception of graduates of mechanical engineering of Technical School Leaving Certificate (TSLC) level perceive about their curriculum after they have entered the job market. The paper is a case study of Balaju School of Science and Technology (BSET) under the Council for Technical Education and Vocational Training (CTEVT) - Nepal in which semi-structured interviews of five graduates were conducted. The empirical research has been confined to exploring the perceptions of TSLC: pre-SLC intake graduates of mechanical trade and working inside Nepal. The study has brought forth that the graduates perceive their curriculum positively as the contents were relevant to the job market and the image of their institute was strong; and but they perceive the curriculum negatively since quite a few modules having high demand in the labour market lacked adequate practice, and a few contents were not updated. Besides, poorly managed infrastructure which was not up-to-date and the lack of professional attitude in the instructors impelled them to perceive their curriculum as less effective. On the other hand, the paper also showed the labour market exploiting the graduates despite the curriculum being market focused and graduates being skilful. The paper provides a thorough perspective of such graduates that may serve as a guideline for curriculum developers to address the identified issues. It also opens up the doors for further research to explore the issues in other technical subjects as well as vocational training programmes.